Membentuk Karakter Kreatif : Bergerak Melalui Stimulus Permainan Tradisional - Budiman, Agus; Karyati, Dewi (Jurnal PGSD, 2021)
This study aimed to obtain result overview of dance learning in dance extracurricular activities as application of creative character education in elementary school. The method used in this research was an experimental method with data collection techniques through observation studies, techniques, literature studies, interview techniques and documentation studies. The sample consisted of 23 elementary school students at SD Lab UPI School. The findings show that the process of strengthening character education in dance extracurricular activities can be realized through various character learning habits that can be done at several stages of learning activities. The conclusion of this study is the strengthening of character education in students can be achieved in extracurricular dance activities through  prayer learning activities, singing national songs, independent and group learning, creative processes, appreciation and creation.